Effect of Total Quality Mangement on Visitor Satisfaction and Its Effect on Service Quality - Zainuddin Latuconsina; Uli Wildan Nuryanto; Pandu Adi Cakranegara; I Nyoman Tri Sutaguna; Samuel PD Anantadjaya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze effect of total quality management on visitor satisfaction and its effect on service quality. The population in this study are library employees at Universitas Pattimura, Ambon. The sampling technique used is purposive sampling, with a number of respondents as many as 33 respondents. Data are collected using a questionnaire as the main instrument and a questionnaire using the likert scale to measure respondents' answers. Hypothesis testing using partial least square test. The results show that total quality management has a positive effect on visitor satisfaction at the Library at Universitas Pattimura, Ambon. Visitor satisfaction has a positive effect on service quality at the Library at Universitas Pattimura, Ambon.